Designing Students’ Writing Skill with the Help of the LEB Android Application - Ulfa Wulan Agustina; Siti Syafa'ah (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Language ability consists of four abilities to master it. The four abilities are speaking, listening, writing, and reading. Speaking can be done spontaneously, but writing must be planned and organized. The purpose of this research is to design an appropriate android application-based learning media to help students develop their English writing skills. This study uses the Research and Development method which was adapted in the development of the ADDIE model. The researcher designed a learning media called